2021
DOI: 10.1093/ecco-jcc/jjab076.449
|View full text |Cite
|
Sign up to set email alerts
|

P325 Real-World Effectiveness And Safety Of Ustekinumab In Patients With Ulcerative Colitis: A Multi-Centre Study

Abstract: Background Pivotal trials have shown that ustekinumab (UST) is effective in ulcerative colitis (UC). However, the population included in these trials do not always represent the cohort of patients treated in the “real world”. In this study, we aimed to describe the effectiveness and safety of UST in a clinical cohort of patients with UC Methods We performed a multi-center cohort study and included patients with active UC star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…In all, 11 studies [6][7][8][9]16,19,20,[22][23][24]26 Between-study heterogeneity was considerable at week 8 (I 2 = 87%) and month 12 (I 2 = 82%), might be not important at weeks 12-16 (I 2 = 26%), and was substantial at month 6 (I 2 = 65%) (Figure 1).…”
Section: Primary Endpoint: Clinical Remissionmentioning
confidence: 98%
See 4 more Smart Citations
“…In all, 11 studies [6][7][8][9]16,19,20,[22][23][24]26 Between-study heterogeneity was considerable at week 8 (I 2 = 87%) and month 12 (I 2 = 82%), might be not important at weeks 12-16 (I 2 = 26%), and was substantial at month 6 (I 2 = 65%) (Figure 1).…”
Section: Primary Endpoint: Clinical Remissionmentioning
confidence: 98%
“…Of the 254 citations identified, 19 studies including 3786 patients with UC were eligible for inclusion in this systematic review (Table S2). [5][6][7][8][9][15][16][17][18][19][20][21][22][23][24][25][26][27][28] In all, 13 studies were reported as full-text articles, and 6 were conference proceedings. According to JBI criteria for quality assessment, 14 studies showed low risk of bias, and 5 articles showed moderate risk (Table S3).…”
Section: Re Sultsmentioning
confidence: 99%
See 3 more Smart Citations